Dinâmica de colisão de multipartículas: simulando a hidrodinâmica de fluidos complexos através de uma aproximação de partículas - Figueiredo, David Oliveira de (2014)
Simulation techniques with a strategy based on particle dynamics are an interesting alternative approach in describing the behavior of complex fluids. In these systems, phenomena occur typically in the range of mesoscopic size (nanometers to micrometers), where the energies are of the order of the thermal energy kT. In many phenomena the microscopic detail of the interaction between the constituents of the system is crucial for the correct description of the physical processes associated, so that a "coarse-graining" approximation, used in a continuous description based on the Navier-Stokes is not appropriate. It is in this context that the method presented here becomes important. Introduced by Malevanets and Kapral in 1999, the stochastic rotation dynamics, or multiparticle collision dynamics, is a simulation method for mesoscopic fluids; which basically consists of alternating streaming and collisions steps in an ensemble of point particles. The collisions are performed by grouping the particles into cells, in which there is conservation of mass, momentum and energy, in addition to meeting the hydrodynamic equations and taking into account the thermal fluctuations of the system. In this work we aim at presenting the multiparticle collision dynamics, through a discussion of its details, features and how the implementation is done in numerical simulations. Moreover, we present some classical hydrodynamics results, obtained from the method presented in this work.